FOSTERING SECONDARY SCHOOL STUDENT’S SPEAKING FLUENCY THROUGH TASK-BASED DIGITAL STORYTELLING - Musawimin, Muhammad (Critical Review of English-Arabic World Journal, 2023)
Learning to speak fluently in English as a Foreign Language (EFL) is crucial for language acquisition. This study focuses on the use of digital storytelling to enhance speaking fluency, addressing a gap in existing research. The case study details a digital storytelling project implemented in Jember Islamic Senior High School with 11th-grade students aged 16 to 17. Through classroom observations, artifact analysis, and semi-structured interviews, the research uncovered three key findings: 1) DST-mediated speaking fluency development, 2) Enhancing students' enthusiasm for acquiring speaking fluency and 3) The enjoyable learning students experience in speaking classroom. The study suggests that emotions and experiences during digital storytelling benefit students and educators, fostering creativity, joy, and enthusiasm in the learning journey, ultimately enhancing speaking skills. In conclusion, the research strongly recommends digital storytelling as an effective learning approach for students aspiring to improve their speaking fluency.